Incorporando comidas e contextos: a alimentação e o corpo nos gruposfoqueiros nas Shetland do Sul (Antártica, século XIX) - Maria Jimena Cruz (2014)
This research seeks to discuss the different ways in which diverse contexts are experienced in the modern world. For this, I develop an analytical model that relates body and alimentary practices dimensions to facilitate the discussion of aspects of the experience of a specific human group. This model is going to be applied to a specific case study; the sealer voyages made during the XIX century. I believe that the sealer industry of the XIX century represent an interesting case study because its part of the mentioned process and the relation between people, things and the world were inserted in it. Thinking that these voyages were conformed by two different but at the same time complementary moments the life on the ships and on the land-, I understand that each one can be addressed through different perspectives, the macro and micro. To approach them, I used two lines of evidence, the voyage diaries published during that period of time in American and British cities and the journals that were related with the industry (Whalemens shipping lists). For the second perspective I studied the material evidence excavated on Cerro Negro and Punta Varadero, two sites localized on the Byers peninsula of the Livingston island (South Shetland, Antarctica).